2017
DOI: 10.1111/cpf.12463
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of the blood–brain barrier transport of large neutral amino acids during acute systemic inflammation in humans

Abstract: We reassessed data from a previous study on the transcerebral net exchange of large neutral amino acids (LNAAs) using a novel mathematical model of blood-brain barrier (BBB) transport. The study included twelve healthy volunteers who received a 4-h intravenous lipopolysaccharide (LPS) infusion (total dose: 0·3 ng/kg), a human experimental model of the systemic inflammatory response during the early stages of sepsis. Cerebral blood flow and arterial-to-jugular venous LNAA concentrations were measured prior to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…6 , 7 ). Arterial concentrations of phenylalanine were also increased after intravenous lipopolysaccharide (LPS) infusion in healthy volunteers 28 . The liver is the main site of phenylalanine metabolism; therefore, deterioration of liver function may reduce this metabolism, raising systemic phenylalanine levels.…”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 ). Arterial concentrations of phenylalanine were also increased after intravenous lipopolysaccharide (LPS) infusion in healthy volunteers 28 . The liver is the main site of phenylalanine metabolism; therefore, deterioration of liver function may reduce this metabolism, raising systemic phenylalanine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found abnormal levels of neurotransmitter precursors, including amino acids, in both the serum and cerebrospinal fluid of patients with SAD [11,12]. The significance of this is unclear but may suggest concurrently deranged levels of neurotransmitters in sepsis and abnormal neurotransmission, however it may also reflect protective mechanisms to detoxify phenylalanine levels [13].…”
Section: Neurotransmissionmentioning
confidence: 99%
“…Blood–brain barrier (BBB), formed by the tight junctions of endothelial cells, is a major barrier for drugs aiming to reach the central nervous system (CNS). Most neuroprotective drugs have nutrition, repair, and protection functions to CNS, which are hindered by the BBB. Only small hydrophobic molecules with low molecular weight can cross it.…”
Section: Introductionmentioning
confidence: 99%